SUBSTITUTED SERVICE IN POLISH CIVIL PROCEEDINGS: SELECTED ISSUES - Kowalik, Emil (Zeszyty Prawnicze, 2026)
The delivery of correspondence in civil proceedings is one of the key elements in the proper course of the judicial process. Defective delivery can lead to serious procedural consequences, even including the invalidity of the proceedings, if, in outcome of a violation of the provisions for delivery, a party has been deprived of the opportunity to defend his rights. That is why ensuring the eﬀective and lawful service of court documents is an important condition which must be met to maintain the standards required for a fair trial and avoid procedural complications. Service of court and procedural documents is therefore a fundamental instrument to ensure the proper course of civil proceedings. Although the preferred and basic form of service is the traditional form of service, consisting in the delivery of the document directly to the addressee, sometimes everyday practice prevents its implementation. In response to such difficulties, the Polish legislator has provided for the application of special forms of called substituted delivery, intended to protect the interests both of litigants and other recipients of court correspondence. This article discusses selected issues concerning substituted delivery in Polish civil proceedings. Aspects concerning potential recipients covered in the discussion include adult members of the addressee’s household, an employee authorized to receive correspondence, and delivery to the administrator or caretaker of the property; with a presentation of the conditions that must be met for such a form to be eﬀective. Special conditions must be met for delivery to a person other than the addressee, e.g. a caretaker or family member, especially if the addressee is not available. In addition, there is an obligation to first attempt service in the traditional manner, and only if that proves impossible to use appropriate methods of substituted delivery. The article analyzes the conditions for eﬀective delivery, including the importance of submitting the letter to the appropriate post office or office of the local authority. If the addressee is not at the address appointed for delivery when the notice is served, the person handling the service is obliged to issue a note advising him in writing that an official letter or notice has been served on him. If there is no response within the specified time limit, a second advice slip must be issued, and this is regarded as the final condition which must be met for the letter or notice to be considered eﬀectively delivered. The mere submission of the letter to the office of the postal operator or local authority will not produce the eﬀects of delivery if the addressee has not been properly notified, in compliance with Polish case law and doctrine. The article emphasizes the importance of observing the procedural requirements of substituted service of court documents, showing that service providers must keep to the applicable regulations and the guidelines of case law and doctrine. It also discusses deadlines and methods of submitting a document, as well as the consequences of ineﬀective service, which is of key importance for the proper course of court proceedings. It indicates that improperly performed service, e.g. without double notification, may result in its invalidity and the need for repeated service, which may delay the entire court process. Eﬀective service is crucial to the ensurance of the proper course of proceedings and protection of the rights of the parties, and its proper implementation requires not only the formal submission of the document, but also proof that the addressee has been properly notified of its submission and has been given the due conditions to receive it.